1987
DOI: 10.1093/ajcn/46.6.968
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of a low-glycemic-index diet

Abstract: Six healthy male volunteers underwent 2-wk metabolically controlled high-glycemic-index (GI) and low-GI diets in random order. Over the low-GI diet significant reductions were seen in serum fructosamine (7.0 +/- 1.0%, p less than 0.01), 12-h blood glucose profile (37 +/- 7%, p less than 0.01), and total serum cholesterol (15 +/- 3%, p less than 0.01). As a measure of insulin secretion, 24-h urinary C-peptide levels were 32 +/- 10% lower (p less than 0.05) after the low-GI than after the high-GI diet. Lower C-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(161 citation statements)
references
References 50 publications
7
147
1
Order By: Relevance
“…Other studies also revealed the potential application of GI in preventing or treating cardiovascular disease (Liu et al, 2000), undesirable lipid profile (Jenkins et al, 1987;Frost et al, 1999;Liu et al, 2001) and cancer Franceschi et al, 2001). However, it is practically difficult to plan a low-GI diet (Raben, 2002) because there is a shortage of low-GI foods in the market and most staple foods have high GI values (Bjorck et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also revealed the potential application of GI in preventing or treating cardiovascular disease (Liu et al, 2000), undesirable lipid profile (Jenkins et al, 1987;Frost et al, 1999;Liu et al, 2001) and cancer Franceschi et al, 2001). However, it is practically difficult to plan a low-GI diet (Raben, 2002) because there is a shortage of low-GI foods in the market and most staple foods have high GI values (Bjorck et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have focused on the role of other dietary factors, such as carbohydrates and the GI values of meals, in promoting or preventing weight gain and obesity (Slabber et al, 1994;Ludwig et al, 1999;Bessesen, 2001). The slower digestion of carbohydrates with low-GI values has been found to be associated with higher satiety (Holt et al, 1992), improved insulin sensitivity (Frost et al, 1999) and other beneficial metabolic effects (Jenkins et al, 1987). A retrospective cohort study showed that body weight and body mass index (BMI) of obese children reduced significantly more in those children receiving low-GI dietary advice as compared to the group receiving advice to reduce fat intake (Spieth et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a group of 32 patients with CHD fed a low-GI diet for 4 weeks, significant improvements in insulin sensitivity were reported as suggested by lower insulin requirements necessary to handle a standard glucose load and by the enhanced insulin-induced glucose uptake in adipocytes (Frost et al, 1996). Low-GI diets have been shown in other studies to reduce blood glucose levels and urinary C-peptide output, as a measure of insulin secretion, also in healthy subjects (Burke et al, 1982;Jenkins et al, 1987b). Low-GI diets also improved glycemic control in diabetic patients, as indicated by reductions in glycosylated Figure 1 Potential mechanism for the relationship between high glycemic index foods and insulin resistance.…”
Section: The Glycemic Index In Diabetesmentioning
confidence: 98%
“…Many factors such as food form, particle size, cooking, processing and starch structure affect the GI (Björck et al, 1994). There is evidence that low GI foods improve blood glucose control in people with diabetes Wolever et al, 1992a;Frost et al, 1994;Järvi et al, 1999;Gilbertson et al, 2001), reduce serum lipids in people with hypertriglyceridaemia (Jenkins et al, 1987a), prolong endurance during physical activity (Thomas et al, 1991), improve insulin sensitivity (Frost et al, 1998) and increase colonic fermentation (Jenkins et al, 1987b;Wolever et al, 1992b). In addition, low GI foods are associated with high HDL cholesterol (Frost et al, 1999) and reduced risk for developing diabetes (Salmeró n et al, 1997a,b) and cardiovascular disease (Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%